How many feces should be sampled from latrines? Spatial sampling biases affecting the dietary analysis of island raccoon dogs. Issue 2 (27th May 2020) - Tsukada, Hideharu; Abe, Kaede; Takatsuki, Seiki; Minami, Masato
Abstract : Biased sampling could affect the results due to the pseudoreplication from the same animal and the spatial heterogeneity of food distribution although sampling methods are not always well discussed in studies of fecal analysis for animal food habits. We investigated the effects of biased sampling in sample size, collection site and its surrounding environment on the fecal analysis using the point frame (%PF) and the frequency of occurrence (%FO) methods of island raccoon dogs Nyctereutes procyonoides, which are opportunistic in food habits and defecate at fixed latrines. Our analyses showed that when the sample size was <30 and <50 in %PF and %FO, respectively, a significant bias was observed, and if the fecal sampling environment was restricted to the inland area, a significant bias occurred even if the sample size was <50 and <70 in %PF and %FO, respectively. If the sampling point was restricted to a specific latrine or the seashore, a significant bias in the dietary analysis could not be eliminated even if the sample size was artificially increased to 100. To avoid biases, spatially biased sampling to collect many feces from a specific latrine should be avoided. It seemed necessary to collect ≥30 and ≥40 fecal samples in %PF and %FO, respectively, from different latrines.